Evaluating the psychometric properties of the Social Identity Questionnaire for Sport (SIQS). (March 2018) - Bruner, Mark W.; Benson, Alex J.
Abstract: Objectives: The strength with which individuals identify with a sport team (i.e., social identity) has important implications for athletes' cognitions, affect, and behavior. Yet there remains ambiguity surrounding the optimal way to conceptualize and thus assess social identity. The purpose of the current study was to examine the psychometric properties of a nine-item version of the Social Identity Questionnaire for Sport (SIQS). Design: Athletes completed a self-report measure of social identity related to sport team involvement. Method: In a sample of 869 youth and young adult athletes ( M age  = 14.84, SD  = 3.79; male = 375; female = 493), we evaluated the psychometric properties of a nine-item version of the Social Identity Questionnaire for Sport (SIQS) by using bifactor analysis and subsequently testing single-factor and three-factor structures. Results: Overall, a theoretically conceived three-factor structure is empirically supported, where ingroup ties, cognitive centrality, and ingroup affect are represented as distinct dimensions of social identity. Empirical support was also found for a global factor of social identity, but only when the residuals among the subscales were correlated. There was support for strong measurement invariance across sexes for the unidimensional and three-factor structure models. Discussion: The findings from the study support the SIQS as a psychometrically sound measure of social identity in sport that can be used to either model social identity along three specific dimensions or as a global construct. Highlights: A nine-item Social Identity Questionnaire in Sport (SIQS) is evaluated. The SIQS is a psychometrically sound measure of social identity. SIQS can model social identity as three dimensions or as a global construct. SIQS exhibited strong measurement invariance across sexes.